1992
DOI: 10.3354/dao014001
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathology of spleen in eel Anguilla Anguilla exposed to a chemical spill in the Rhine River

Abstract: Structural alterations in the spleen of eel Anguilla anguilla L., following exposure to a chemical spill in the Rhine h v e r in 1986, were investigated by means of light and electron microscopy. Relative abundance of reticulum and blood cells was quantified in comparison to controls. The data presented provide evidence of profound damage to the spleen and its cellular components. Histological and cytological modifications varied within a wide range from minor changes to cell death. Major cytological alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
2
15
1
2
Order By: Relevance
“…These results are in agreement with [56] who clarified that necrosis and vacuolation in splenic tissue of European eel Anguilla anguilla following stress of fasting resulting in impairment of normal physiology of fishes. Deposition of haemosiderin leads to pathological state known as haemosiderosis [57].…”
Section: Discussionsupporting
confidence: 82%
“…These results are in agreement with [56] who clarified that necrosis and vacuolation in splenic tissue of European eel Anguilla anguilla following stress of fasting resulting in impairment of normal physiology of fishes. Deposition of haemosiderin leads to pathological state known as haemosiderosis [57].…”
Section: Discussionsupporting
confidence: 82%
“…The MMB's were so conspicuous and unique in profiles of HCC cells, in the present study, that they gave the impression of being real antemortem alterations and structural additions to these presumed neoplastic cells. Further indications that the MMB's may be genuine pathological changes in these chemically induced HCC cells are the reports of similar MMB's in hepatomas of mammals (Ghadially 1975), in neoplastic hepatocytes in bullhead catfish (Hampton et al 1988), in toxicant-exposed non-neoplastic fish hepatocytes (Braunbeck & Volkl 1991), and in cells from eels exposed to mixed toxicants (Spazier et al 1992). In these reports, as in the present report, the MMB's appear to occupy the intermembranous spaces of hepatocyte mitochondria.…”
Section: Discussionsupporting
confidence: 82%
“…Such a qualitative alteration as MMB's cannot be related solely to presumed neoplastic transformation in the present study, because even though Hampton et al (1988) found myelin figures in bullhead HCC cells, Braunbeck & Volkl (1991) found MMB's in eel nonneoplastic hepatocytes and Spazier et al (1992) found them in eel spleen cells that were not neoplastic, but which were biochemically altered following exposure to dinitro-o-cresol (DNOC) in both the polluted Rhine River and in laboratory experimental exposures. Therefore, if MMB induction is not a fixation artifact, but results directly or indirectly from chemically induced cytotoxic effects (e.g.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Une autre étude a été entreprise pour tester les effluents toxiques du Rhin sur l'anguille (SPAZIER et al, 1992), qui a révélé l'existence de lésions cellulaires de la rate traduisant des anomalies de phagocytose et une diminution de la défense immunitaire cellulaire. Certaines affections telles que la nécrose printanière de l'anguille («spring ulcer disease»), sous la forme de nécroses et hémorragies tégumentaires, ont été rapportées à des pollutions multifactorielles (JENSEN et al, 1983 ;DALSGAARD, 1987) (Fleuve Ems, en 1985: KOOPS et HARTMANN, 1987TARASCHEWSKI etal., 1987), Pays-Bas (juillet 1985 : VAN BANNING et al, 1985), Belgique (décembre 1985: BELPAIRE et al, 1987et 1989a, Danemark (1986: KOIE, 1988b, Suède (1988: HOGLUND et ANDERSSON, 1993, Hongrie (septembre 1990: SZEKELY etal., 1991), Grande Bretagne (fin 1987: KENNEDY et FITCH, 1990, Italie (CAN ESTRIN l-TROTTI, 1987), Espagne (avril 1987: BELPAIRE etal., 1989b Ce ver hématophage se localise, à l'état adulte, dans la vessie gazeuse, les larves L 3 se développant dans la paroi de cet organe.…”
Section: F -Contaminations Multifactorielles De Certains Milieux Natuunclassified